The role of the central banks in regional integration: Analysing financial convergence initiatives led by the Central Bank of Brazil and the Reserve Bank of India towards a regional payment system in MERCOSUR and SAARC - Campos, Andre Sanches Siqueira (2023)
Central banks play a significant role in promoting regional economic, financial, and monetary cooperation by upgrading the payment and settlement systems. However, close coordination and cooperation require facilitating the implementation of reforms at domestic and cross-border levels in order to benchmark with international standards. This context tends to be influenced by the interests of developed countries and the dimensions of regulatory globalisation promoted by international bureaucracies such as the BIS, IMF, World Bank, UN Regional Commissions, and Regional Development Banks in global financial governance. This framework of political interactions shapes the behaviour of central banks, which may drive or constrain regional integration. This research aims to analyse the role of the Central Bank of Brazil and the Reserve Bank of India towards regional financial cooperation identifying instruments that foster, gridlock, or redefine cooperation, particularly within the framework of MERCOSUR and SAARC. Since the mid-2000s, these central banks have set financial convergence initiatives with the purpose of developing a regional payment system at MERCOSUR and SAARC, which facilitate intra-trade performance and enhance foreign direct investments and, consequently, improve expectations of deepening regional integration in South America and South Asia. This research contributes to Regional Integration studies by filling the gaps in the existing literature addressing how central banks provide an effective institutional arrangement for regional organizations to achieve political and economic objectives. This qualitative document analysis research is based on Rational Choice Institutionalism and supported by Historical Institutionalism to approach critical junctures. It approaches multiple sources of data based on central banks, national governments, and regional organizations supported by existing literature. Findings from empirical evidence of the selected case studies demonstrated that the central banks of Brazil and India tend to be reluctant to deepen regional integration because of the existing economic, political, and institutional asymmetries that shape their regions. Central banks strengthened regional financial cooperation initiatives as they reduced the economic risks implicit in the integration process, aiming to protect the stability of their national financial system, foster national development, and preserve the political autonomy of Brazil and India, which provides political ground for the contestation of the Global Financial Governance.